Competitive exclusion products as an antimicrobial alternative to control Salmonella Heidelberg in broilers - Kolososki, Isis M.M. [UNESP]; Saraiva, Mauro M.S. [UNESP]; Nascimento, Camila F. [UNESP]; Campos, Isabella C. [UNESP]; Lima, Túlio S. [UNESP]; Ferreira, Viviane A. [UNESP]; Rabelo, André L.C. [UNESP]; Almeida, Adriana M. [UNESP]; Berchieri, Angelo [UNESP] (Oxford University Press (OUP), 2024)
Intestinal infections caused by non-typhoidal Salmonella spp., along with antimicrobial resistance spread are a major food safety concern worldwide. Here, we evaluate the potential of competitive exclusion products developed by anaerobic or aerobic conditions to control systemic infection, cecal colonization, fecal excretion, and improve the intestinal health in broilers challenged by Salmonella Heidelberg (SH). A total of 105 day-old chickens were randomly distributed into three experimental groups: A (untreated control), B (treated with anaerobic culture), and C (treated with aerobic culture). During 21 days, morphometric parameters of the small intestine were analyzed using microscopy, fecal excretions by cloacal swabs, systemic infection, and cecal colonization by colony-forming unit counts (CFU/g). The results indicated the lowest number of positive swabs (45.33%) recovered from Group C, followed by Group B (71.8%) and Group A (85.33%). The bacterial enumeration revealed the lowest amounts in Group C at the necropsy realized in 5-, 7-, and 14-days post-infection (DPI) (P = 0.0010, P = 0.0048, and P = 0.0094, respectively). Statistical differences between intestinal morphometrics were observed in the Group C at 21 DPI. Our results suggest that the product developed under aerobic conditions can improve intestinal health, protecting birds against SH. Impact Statement This study represents a promising methodology based on the competitive exclusion products developed by both anaerobic or aerobic serial dilutions of adult health-broiler feces to be used in the development of a viable and functional protocol to mitigate Salmonella spp. infections and may indicate an alternative to the use of antimicrobials as well.
Keywords: antimicrobial resistance; antimicrobials; One Health; probiotics